Datin Paduka Shahaneem Hanoum N. N. Dadameah / Noor Eliani Noor Rawi and Siti Syazwana Che Said - Noor Rawi, Noor Eliani; Che Said, Siti Syazwana (2011)
Datin Shahaneem Hanoum was among the first women joined the PPAS library corporation established to attract and encourage interest in reading among local residents. The librarian who uphold the library in society and produce many generations a love of books. She is also a writer and an activist in various associations and advisors. She is a director of PPAS is the longest serving the corporation in charge of public libraries in PPAS for 34 years until her retirement in 2006. Shahaneem Hanoum should become an idol to every community because of her service to a very large increase in participation in the library.